Investigating information seeking anxiety among postgraduate students : development and validation of a multidimensional scale / Mohammadamin Erfanmanesh - Erfanmanesh, Mohammadamin (2012)
The current study aims to determine whether a valid and reliable instrument could be developed and validated to measure levels of anxiety experienced by postgraduate students during the information seeking process. It also attempts to determine the prevalence and correlates of the information seeking anxiety among postgraduate students at a research intensive university in Kuala Lumpur, Malaysia. Results of the study indicated that the newly developed scale, the Information Seeking Anxiety Scale (ISAS), had satisfactory face, content, and construct validity as well as internal reliability. The Information Seeking Anxiety Scale (ISAS) contains thirty-eight (38) 5-point Likert-format items that measures seven (7) facets of information seeking anxiety construct. The first factor of the Information Seeking Anxiety Scale, barriers associated with libraries, consisted of ten (10) statements which explained 24.423% of the total variance. The second factor, barriers associated with information resources, contained seven (7) statements that were accounted for 7.315% of the total variance. The third dimension of the scale contained three (3) statements and accounted for 5.150% of the variance. This factor was labelled barriers associated with computers, the Internet and electronic resources. The fourth factor, technological barriers, represented 4.181% of the variance and included six (6) statements. Factor five, Affective barriers, comprised five (5) statements and accounted only for 3.430% of the variance. Three (3) statements were loaded on the sixth factor, barriers associated with topic identification, which explained 2.865% of the total variance. Finally, the seventh factor comprised four (4) items and explained only 2.787% of the variance. Results of the study revealed that postgraduate students at a research-intensive university in Malaysia had mean score of 88.31 for overall information seeking anxiety. This indicated that while information seeking anxiety is present, overall levels are not severe. They had the greatest levels of information seeking anxiety as it pertained to the “barriers associated with libraries” with a mean score of 23.261. Conversely, they reported to have experienced the least levels of information seeking anxiety as it pertained to “barriers associated with computers, the Internet and electronic resources” dimension with a mean score of 7.146. Gender, level of study, major, age and frequency of library use were found to be antecedents of the information seeking construct using a series of independent sample ttests, one-way analysis of variance and Pearson product moment correlation coefficient tests. Conversely, nationality, information literacy skills instruction received and frequency of the Internet use had no statistically significant effect on various dimensions of the information seeking anxiety construct.